2003
DOI: 10.1055/s-2002-36173
|View full text |Cite
|
Sign up to set email alerts
|

Chest Sonography in the Diagnosis of Pulmonary Embolism: A Comparison with MRI Angiography and Ventilation Perfusion Scintigraphy

Abstract: A negative sonographic study cannot rule out PE with certainty. However, a chest sonography is of acceptable diagnostic value in patients with suspected PE and may be used as an adjunct or guide to more established methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0
4

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 13 publications
0
25
0
4
Order By: Relevance
“…Sonographic findings of PE on transthoracic US (TUS) are well described [13][14][15][16][22][23][24][25][26][27][28][29] and correlate with the pathophysiologic results found on autopsy in patients diagnosed with PE and on helical CT. 28,30,31 Sonomorphology can be divided into parenchymal and pleural pathology. Typical parenchymal pathology includes multiple hypoechoic areas of lung tissue extending to the pleura.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sonographic findings of PE on transthoracic US (TUS) are well described [13][14][15][16][22][23][24][25][26][27][28][29] and correlate with the pathophysiologic results found on autopsy in patients diagnosed with PE and on helical CT. 28,30,31 Sonomorphology can be divided into parenchymal and pleural pathology. Typical parenchymal pathology includes multiple hypoechoic areas of lung tissue extending to the pleura.…”
Section: Discussionmentioning
confidence: 99%
“…13,14,[28][29][30] Pleural findings consist of localized or basal pleural effusions and can be found in up to two-thirds of patients with PE. [22][23][24][25][26][27] They correspond to the site of the parenchymal lesion. 14,[22][23][24][25][26][27][28][29] Interestingly, several investigators have found that the majority of detected PEs are found in the lower lung lobes, also noting that the localization of the parenchymal and pleural defects correlate with the area of pleuritic chest pain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This translates to a positive predictive value of 95 % and a negative predictive value of 75 %. Another study supported these results, finding that the presence of round or wedge-shaped densities on thoracic ultrasound is predictive of PE (sensitivity 81 %, specificity 84 %) [14]. In both studies, the incidence of PE was high (55.1 and 65.5 %, respectively) and therefore the positive predictive value may be lower in a general ICU population with a lower incidence of PE.…”
Section: Pulmonary Embolismmentioning
confidence: 72%
“…On the other hand, ventilation/perfusion lung scan is often not sufficiently conclusive [6][7][8], although it is sometimes used [9,10].…”
mentioning
confidence: 99%